Television and common knowledge - Gripsrud, Jostein, 1952- (Comedia series., 1999)
Television and Common Knowledge considers how television can facilitate a well-informed citizenship in a fragmented modern society. The contributors investigate television's role as a means of producing and disseminating knowledge.